Tourism and Sustainable Finance - John Francis T. Diaz (Jurnal Ekonomi dan Bisnis Jagaditha, 2019)
This study addresses the greatly positive effects of tourism and the finance against the world problems. To explore the issues, explorative study was applied in searching for the conditions in the development of tourism and finance. The results indicate that both the finance and the tourism sectors can work together to develop environmentally and socially responsible solutions to help address world problems.